Wild birds in captivery: a threat to biodiversity in Cuba - Armiñana-García, Rafael (2024)
Wildlife and biodiversity help preserve the strength of ecosystems, which in turn support sustainable food systems and agriculture. Likewise, the conservation and sustainable management of wildlife helps to minimize hunger and poverty. The research carried out in the town of Manicaragua, province of Villa Clara, in the Republic of Cuba, had as its objective: to determine the species of migratory birds that are in captivity by the inhabitants of the town of Manicaragua, both in the urban and rural areas, and their possible commercialization. For the development of the research, methods of information collection and methods of processing the information collected were used, such as interviews, participatory observation, review of historical-logical documents, deductive-demonstrative and statistical and mathematical methods among which the descriptive statistical method is emphasized. A total of 360 homes were visited and 172 residents were interviewed, in the center of the town of Manicaragua and its outskirts. The presence of 29 species of wild birds in captivity was confirmed, of which some are in some category of threat, according to the red list of Cuban fauna. It is necessary to make a call to the population about the effects that this may cause to Cuban biodiversity.